Epidermolysis bullosa - Tasic-Uros, Danijela; Andjelic, Sladjana; Stefanovic, Ivana; Milivojcevic Bevc, Ivana; Savic, Nikola (Halo 194 Scientific Journal of Emergency Medicine, 2024)
Epidermolysis bullosa (EB) is a hereditary multisystemic disease caused by genetic defects in the structural proteins of the skin. Depending on the type of disease, symptoms vary from localized fragility and bullae to a widespread generalized form, including extracutaneous disease. In the most severe forms, EB leads to death in the earliest period of life. The treatment of EB is complex and usually requires the involvement of several different specialists. In the absence of curative therapy, treatment is oriented towards supportive care, control of disease symptoms and prevention of mild to severe complications. A new hope for the treatment of wounds in patients with dystrophic form of EB, older than 6 months, is vector gene therapy Vyjuvek (beremagene geperpavec) based on herpes simplex virus type 1.